Antecedents of Zakat payers' trust: the case of Nigeria - Abioye, Mustafa Murtala Oladimejiimeji; Mohamad, Muslim Har Sani; Adnan, Muhammad Akhyar (International Islamic University Malaysia, 2011)
Zakat payers’ trust is vital to zakat organizations because its absence will undermine the institutional effectiveness of zakat. Unlike other forms of voluntary donations, zakat is a religious duty guided by divine rules. However, zakat payers have choices to turn to collection channels of their preference either through governmental or voluntary zakat institutions. With increasing number of charitable organizations, competition for limited zakat and other donation becomes intense. Understanding the zakat payers’ compliance behavior is central to the development of zakat institutions because their effectiveness to help the poor and other beneficiaries is heavily dependent on zakat collection. However, such studies are sparse. Therefore, the aim of the paper is to fill this gap by developing and validating the model of zakat payers’ trust in zakat institutions. The constructs of trust’s antecedents were drawn from resource dependence theory, legitimacy theory, and donor trust literature. Through structural equation modeling test, we found perceptions of board capital, legitimacy management and stakeholders’ orientation are important to determine zakat payers’ trust. The trust model represents the main contribution of this study. Importantly, necessity of understanding zakat payers’ trust are more pertinent at the place where proper zakat administration is still in its infancy stage as in the case of Nigeria.